Hubungan antara Pemenuhan Kebutuhan Tidur dengan Penurunan Daya Ingat pada Lansia - Faridatul Istibsaroh (Indonesian Health Science Journal, 2021)
Introduction: The aging process in human lifenormally causes a decrease of brain function and especially a change in memory capacity. Memory decline happens only in certain aspects of memory, such as the ability to receive information (acquisition) and rediscover the new information. One of the influencing factors is the fulfiment of sleeping at the night. Objective: This research aims at determining the relationship between the fulfilment of sleeping and memory loss in the elderly people. Methods: The research method is correlation analytic design using crossectional approach, and its population are 46 respondents. The sampling technique uses purposive sampling. The data is collected from respondents using questionnaires and interviews, then the results is analyzed Spearman test with degrees of significance (α <0.05) uses SPSS 16.0. Result: The results show that the respondents whom have a high fulfilment of sleep are 22 respondents (67%) and 18 respondents (55%) have cognitive impairment, the value of ρ = 0.000 (α <0.05) and the value of r = 0.763, this indicates that there is a relationship between the fulfilment of sleeping need and memory decline on the elderly people. Conclusions: The study concludes that the fulfillment of sleeping needs has a significant relationship with memory decline in the elderly. Therefore, there are some treatments which can be done such as involving the elderly to read, write, and discuss in groups, take a walk in the morning for 15 minutes and to encourage them to get enough sleep the night ± 5-6 hours a day.